Goal setting in pediatric rehabilitation - Beate Ytreberg (Fysioterapeuten, 2017)
Introduction: Goal setting is paramount in definitions of rehabilitation; in laws, regulations and in descriptions of clinical rehabilitation. Theoretical foundation and evidence for the use of goal setting in pediatric rehabilitation are unclear, which is ethically challenging. Main part: Goal setting serve several purposes. This paper discusses theoretical foundation, evidence and purpose for the use of goals in pediatric rehabilitation, especially in relation to meaning and play. Sum up: Goal setting is important and complicated. We need more knowledge in connection with goal setting within pediatric rehabilitation contexts.